Growth of immature rubber trees planted in abandoned paddy field and upland areas in relation to soil properties and leaf nutrients - Jumpen Onthong; Khwunta Khawmee; Chutharmard Keawmano (Songklanakarin Journal of Science and Technology (SJST), 2017)
Although lowland area is not suitable for rubber production, rubber trees are currently extended into abandoned paddy fields. This study investigated rubber growth, soil properties and leaf nutrients of immature rubber trees planted in lowland and upland plantations. Nine soils (0-30 cm depth) in both poor and good productive lowland and upland plots from three districts in Songkhla province were sampled for some physical and chemical analysis and leaf samples were also performed for nutrient analysis. Growth of rubber trees was recorded. Results showed that soil in the lowland had finer texture compared with the upland soil, resulting in tendency of higher organic matter, total N and CEC. In addition, high DTPA Mn and soil mottles are generally found in a profile of the lowland soil. However, immature rubber trees planted in the good productive lowland plot grew as similar as in the upland soil. Whereas, in the poor productive plot, rubber growth was limited and concentrations of leaf N, P and K tended to be lower than those in the upland soil, in contrast to leaf Mn. These findings revealed that soil mottles within 0-30 cm are markedly indicator of limitation of the lowland for rubber cultivation.